1999
DOI: 10.1002/(sici)1098-2396(19990315)31:4<250::aid-syn2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Castration differentially alters [3H]nisoxetine binding to norepinephrine uptake sites in olfactory bulb and frontal cortex of male rats

Abstract: In the present study, [3H]nisoxetine binding to norepinephrine (NE) uptake sites and [3H]norepinephrine uptake were investigated within olfactory bulb (OB) and frontal cortex homogenates from intact and castrated male rats. Statistically significant reductions in the number of [3H]nisoxetine binding sites (Bmax) were found in OB from the castrates, while significantly increased Bmax values were obtained in the frontal cortex. Castration also significantly altered the affinity (Kd) of [3H]nisoxetine binding in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
1
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
4
1
0
Order By: Relevance
“…5, 6 A,C). These values are comparable to those previously reported for rat brain homogenates (Tejani-Butt, 1992, Vathy et al, 1997, Shang et al, 1999). Across all of the 4 and 28-day treated groups, values of ligand binding affinity for the caudate nucleus were similar to corresponding controls.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5, 6 A,C). These values are comparable to those previously reported for rat brain homogenates (Tejani-Butt, 1992, Vathy et al, 1997, Shang et al, 1999). Across all of the 4 and 28-day treated groups, values of ligand binding affinity for the caudate nucleus were similar to corresponding controls.…”
Section: Resultssupporting
confidence: 92%
“…Nonetheless, as expected maximal numbers of binding sites in the controls were higher in prefrontal cortex (~135–300 fm/mg protein) than in sensorimotor cortex (~150–250 fmol/mg protein) or caudate nucleus (~100–135 fmol/mg protein, Figs. 5, 6B, D) and showed values that on average were comparable to those previously reported for rat brain homogenates (Tejani-Butt, 1992, Vathy et al, 1997, Shang et al, 1999). Visual inspection of the data further showed that for the control and experimental groups alike variance in the data was typically accounted for by single outliers in the data, that for the most part the tissue-specific values that were obtained across these groups were largely overlapping and that there were no obvious group trends in these data (Figs.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The K m of Na + -dependent [ 3 H]NE uptake in astrocytes was only two-fold lower than that in COS-7 cells expressing the rat NET (Paczkowski et al 1999), suggesting the existence of a high-affinity NE uptake system in rat astrocytes. The V max of Na + -dependent [ 3 H]NE uptake in rat cortical astrocytes was 1.41 pmol/mg protein/min, a value very similar to that previously reported for rat cortical synaptosomes (1.63 pmol/mg protein/min reported by Shang et al 1999). Furthermore, the NE transport system in astrocytes appears to be sensitive to both Na + , and ouabain (Na + -K + ATPase inhibitor).…”
Section: Discussionsupporting
confidence: 89%
“…1999), suggesting the existence of a high‐affinity NE uptake system in rat astrocytes. The V max of Na + ‐dependent [ 3 H]NE uptake in rat cortical astrocytes was 1.41 pmol/mg protein/min, a value very similar to that previously reported for rat cortical synaptosomes (1.63 pmol/mg protein/min reported by Shang et al . 1999).…”
Section: Discussionsupporting
confidence: 89%